Implementation and Operational Research: Effects of Antenatal Care and HIV Treatment Integration on Elements of the PMTCT Cascade. (15th August 2015) - Turan, Janet M.; Onono, Maricianah; Steinfeld, Rachel L.; Shade, Starley B.; Owuor, Kevin; Washington, Sierra; Bukusi, Elizabeth A.; Ackers, Marta L.; Kioko, Jackson; Interis, Evelyn C.; Cohen, Craig R.
Abstract : Background: Integrating antenatal care (ANC) and HIV care may improve uptake and retention in services along the prevention of mother-to-child transmission (PMTCT) cascade. This study aimed to determine whether integration of HIV services into ANC settings improves PMTCT service utilization outcomes. Methods: ANC clinics in rural Kenya were randomized to integrated (6 clinics, 569 women) or nonintegrated (6 clinics, 603 women) services. Intervention clinics provided all HIV services, including highly active antiretroviral therapy (HAART), whereas control clinics provided PMTCT services but referred women to HIV care clinics within the same facility. PMTCT utilization outcomes among HIV-infected women (maternal HIV care enrollment, HAART initiation, and 3-month infant HIV testing uptake) were compared using generalized estimating equations and Cox regression. Results: HIV care enrollment was higher in intervention compared with control clinics [69% versus 36%; odds ratio = 3.94, 95% confidence interval (CI): 1.14 to 13.63]. Median time to enrollment was significantly shorter among intervention arm women (0 versus 8 days, hazard ratio = 2.20, 95% CI: 1.62 to 3.01). Eligible women in the intervention arm were more likely to initiate HAART (40% versus 17%; odds ratio = 3.22, 95% CI: 1.81 to 5.72). Infant testing was more common in the intervention arm (25% versus 18%), however, not statistically different. No significant differences were detected in postnatal service uptake or maternal retention. Conclusions: Service integration increased maternal HIV care enrollment and HAART uptake. However, PMTCT utilization outcomes were still suboptimal, and postnatal service utilization remained poor in both study arms. Further improvements in the PMTCT cascade will require additional research and interventions.